Prey preference of four species of forest spiders to Spodoptera litura and Plutella xylostella - Lau, Wei Hong; Mohd Arif, Mohd Huzaifah; Chooi, Y. S. (Universiti Putra Malaysia Press, 2012)
The prey preference of Heteropoda garciai, Olios mahabangkawitus, Ctenus floweri, and Pardosa apostoli was examined on Spodoptera litura and Plutella xylostella in laboratory. These spiders showed a clear preference for P. xylostella compared to S. litura. However, there was no significant difference observed between the second and third instars larvae of P. xylostella. Similarly, the size of prey was not an important factor in the prey selection by H. garciai, O. mahabangkawitus in this study. P. apostoli showed higher preference on smaller sized S. litura larvae.